Student perceptions and achievement in a university blended learning strategic initiative - Owston, Ron; York, Dennis; Murtha, Susan (The Internet and higher education, 2013)
Examined in this study is the relationship between student perceptions in blended learning courses and their in-course achievement. The research was conducted at a large urban university that embarked on a major initiative to scale-up blended learning across its campus. Student perceptions (N=577) were assessed in four areas deemed important to the university: overall satisfaction with blended learning, convenience afforded by blended learning, sense of engagement in their blended course, and views on learning outcomes. Final course grade was the dependent variable and cumulative grade point average was the covariate in an ANCOVA design. A remarkably strong relationship was found between perceptions and grades. Compared with low achieving students, high achievers were the most satisfied with their blended course, would take one again, and preferred the blended format more over fully face-to-face or online. High achievers also found blended courses more convenient, more engaging, and they felt that they learn key course concepts better than in other traditional face-to-face courses they have taken. An implication of the study is that low achievers may not be able to cope with the blended environment as well their high achieving peers. Therefore, when scaling up blended learning institutions may want to consider offering students a choice of whether to enroll in blended or fully face-to-face course sections where feasible, especially in subject areas that students find difficult. ► Student perceptions of blended learning and achievement examined. ► Setting was a large urban university embarking on a major blended initiative. ► High achieverspreferred the blended format over fully face-to-face or online. ► Low achievers may have difficulty coping with the blended environment.